2018
DOI: 10.1158/1078-0432.ccr-17-3702
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Profiling of DNA Repair Defects in Breast Cancer Identifies a Novel Class of Endocrine Therapy Resistance Drivers

Abstract: This study was undertaken to conduct a comprehensive investigation of the role of DNA damage repair (DDR) defects in poor outcome ER disease. Expression and mutational status of DDR genes in ER breast tumors were correlated with proliferative response in neoadjuvant aromatase inhibitor therapy trials (discovery dataset), with outcomes in METABRIC, TCGA, and Loi datasets (validation datasets), and in patient-derived xenografts. A causal relationship between candidate DDR genes and endocrine treatment response, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 51 publications
4
79
0
Order By: Relevance
“…In recent years, detailed information regarding prognosis evaluation for cancer patients can be effectively provided by genome‐wide expression profiling detection . Numerous studies have evaluated the prognostic roles of array‐based gene expression signatures acquired from tumours .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, detailed information regarding prognosis evaluation for cancer patients can be effectively provided by genome‐wide expression profiling detection . Numerous studies have evaluated the prognostic roles of array‐based gene expression signatures acquired from tumours .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, detailed information regarding prognosis evaluation for cancer patients can be effectively provided by genome-wide expression profiling detection. [14][15][16][17] Numerous studies have evaluated the prognostic roles of array-based gene expression signatures acquired from tumours. 14,18,19 Several gene signatures have also been established to distinguish the prognosis of patients beyond the BC clinicopathologic features; however, most of them are not used clinically.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…cDNA was synthesized using the superscript kit (Invitrogen). Quantitative PCR (qPCR) was carried out using Syber Green master mix for target genes and normalized to the housekeeping genes GAPDH or Β-actin using the ΔΔC t method [30]. Primers were designed with Roche Universal Probe Library Assay Design software.…”
Section: Rna Isolation and Rt-pcrmentioning
confidence: 99%
“…Recently, copy number variation analysis of the COSMIC and TCGA databases has clearly shown that, among all DNA repair proteins, NEIL2 is the most affected in various cancers, and its level is generally low (25). A mutant or functional variant of NEIL2 was also reported as a risk factor for lung cancer and squamous cell carcinoma in the oral cavity (26)(27)(28)(29), and the loss of NEIL2 is associated with poor survival in patients with estrogenreceptor positive breast cancer (30).…”
Section: Introductionmentioning
confidence: 99%